ANALISIS PRAKTIK MARKETING DALAM MENUMBUHKAN MINAT BERWIRAUSAHA PADA SISWA KELAS X SMKK IMMANUEL 2 - Erwan, Kristianto; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to find out how the interests of entrepreneurship students through marketing practices of SMKK Immanuel 2. The method used in this study was descriptive method with a form of qualitative research. The data sources in this study were SMKK Immanuel 2 teachers and students. The data collection techniques and tools used were interview guides and documentation. The indicators are seen from marketing practices and interests in entrepreneurship, (1) self-confidence and optimism (2) task-oriented and results (3) risk taking (4) leadership (5) horizon (6) future-oriented. The results showed that self-confidence and optimism were very high for each student, task-oriented and results were also good, where students completed assignments to obtain results, dare to take risks seen in students although there are some who have not dared to take risks, leadership is not fully owned by students, horizon has been seen, students want to try something new, and future-oriented already have, students have their own vision and mission, and marketing practices that exist in SMKK Immanuel 2 namely students are asked to make unique products and interesting with innovation and creativity and then marketed in schools and outside schools in a personal selling manner and through social media. Â Keywords: Interest in Entrepreneurship, Practice of MarketingÂ